2014
DOI: 10.1007/978-3-662-44774-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Anonymity in Bitcoin

Abstract: Bitcoin is a peer-to-peer cryptocurrency that prevents double spending using a distributed public ledger (known as the blockchain). Due to this, true anonymity is not present in Bitcoin because funds can be traced as they pass via different addresses. It is sometimes possible to link various addresses and obtain information not apparent in the beginning (such as loops). We present a method to enhance the anonymity of Bitcoin-type cryptocurrencies. Our method uses a new primitive known as one-way aggregate sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The test results showed that linking the input and output transactions was possible in 1 out of 3 tested services. Other than mixing techniques, Saxena et al [28] suggest use of composite signatures to prevent linking between sending and receiving addresses.…”
Section: Classification Of the Relevant Papersmentioning
confidence: 99%
“…The test results showed that linking the input and output transactions was possible in 1 out of 3 tested services. Other than mixing techniques, Saxena et al [28] suggest use of composite signatures to prevent linking between sending and receiving addresses.…”
Section: Classification Of the Relevant Papersmentioning
confidence: 99%
“…The input address of a transaction is derived from the output of the previous transaction, which is used as the input of other transactions, as depicted in Figure 1(a). However, there are some defects in the anonymity of blockchain addresses that allow the attackers to infer the relation between the addresses and the actual identity of a user [15][16][17]. There are three common defects.…”
Section: Transactionsmentioning
confidence: 99%
“…For Progressive Mining (Section III-D), acknowledgments are composite signatures [18]. Each node in the DAG branch composes its signature with the initial signature generated by the DAG root, forming a composite signature that contains the signature of each node involved in the task.…”
Section: E Acknowledgmentsmentioning
confidence: 99%